Public Attention and Auditor Behavior: The Case ofHurun Rich Listin China - WU, DONGHUI; YE, QING (Journal of Accounting Research, 2020)
ABSTRACT Adverse client publicity can entail regulatory scrutiny over audited financial statements and impose political costs on auditors. We use the changes in client publicity caused by their controlling owners’ presence on the Hurun Rich List (the rich listing) in China to test the hypothesis that auditor conservatism increases with client publicity. Our evidence indicates auditors issue more adverse audit opinions to clients and charge higher fees following the rich listing events. Moreover, we observe that auditors strategically respond to clients with different attributes—for clients whose owners accumulated wealth in a more questionable manner, auditors choose more stringent audit reporting to better defend themselves from regulatory scrutiny; for clients without such attributes, auditors primarily rely on increasing audit fees to cope with any post‐listing increase in audit risks. Our analyses also suggest the impacts of rich listings tend to be concentrated among large audit firms with stronger reputation concerns or among engagement auditors with more conservative reporting styles. By showing how auditors manage political risks associated with heightened public scrutiny, we contribute to both the auditing and political cost literature.